Ethics and human rights in HIV-related clinical trials in Africa with specific reference to informed consent in preventive HIV vaccine efficacy trials in South Africa - Viljoen, Frans (University of Pretoria, 2013)
Thesis (LLD)--University of Pretoria, 2007.